Answer: -3, -2, -1, 2
====================================================
Step-by-step explanation:
Set each factor equal to zero and solve for x. I'm using the zero product property which says A*B = 0 leads to either A = 0 or B = 0.
Let's apply that idea to the first factor.
x^2+4x+3 = 0
(x+1)(x+3) = 0
x+1 = 0 or x+3 = 0
x = -1 or x = -3 are two roots
-------------
Do the same for the other factor as well.
x^2 - 4 = 0
(x-2)(x+2) = 0 .... difference of squares rule
x-2 = 0 or x+2 = 0
x = 2 or x = -2 are another two roots
--------------
In total, the four roots are:
Side note: The term "root" is the same as the zeros of a polynomial. Visually, this corresponds to the x intercepts. Plugging any of those four items into p(x) will lead to p(x) = 0.